Anna Netrebko - The Woman, the Voice - Gounod, Charles; Puccini, Giacomo; Mozart, Wolfgang Amadeus; Bellini, Vincenzo; Dvorák, Antonín (Deutsche Grammophon, 2004)
Here is a singer who simply has it all: A voice of astounding purity, precision and scope, extensive dynamic and tonal range, imagination, insight and wit - all combined with a dazzling charisma that makes it all but impossible to look away when she is performing. [San Francisco Chronicle]